Predictors of outcome among patients on extracorporeal membrane oxygenation as a bridge to lung transplantation. Issue 7 (10th June 2017) - Banga, Amit; Batchelor, Elizabeth; Mohanka, Manish; Bollineni, Srinivas; Kaza, Vaidehi; Mullins, Jessica; Tran, Melissa; Bajona, Pietro; Peltz, Matthias; Wait, Michael; Torres, Fernando
Abstract: Background: There is a lack of data regarding clinical variables associated with successful bridge to lung transplantation (LT) using extracorporeal membrane oxygenation (ECMO) support. Methods: We reviewed the institutional database for patients supported with veno‐venous (VV) or veno‐arterial ECMO as a bridge to LT (n=25; mean age: 50.6±14.2 years). We recorded clinical and laboratory variables, findings on echocardiogram and development of organ dysfunction along with hospital and one‐year survival. Variables were compared between patients successfully bridged to LT versus those who were not. Results: The most common diagnostic group was interstitial lung disease (18/25, 72%). VV‐ECMO was used in the majority (84%). Fifteen patients (60%) were successfully bridged to LT, and the majority were alive at 1 year (14/15, 93.3%). The presence of right ventricular systolic dysfunction on pre‐ECMO echocardiogram was associated with increased risk of unsuccessful bridging (OR, 95% CI: 2.67, 1.01‐6.99, P =.041). While on ECMO, trough albumin levels <2.5 gm%, peak blood urea nitrogen levels >35 mg/dL and positive fluid balance were also associated with failure to bridge to LT. Conclusions: Among patients awaiting LT, the presence of RV systolic dysfunction before ECMO initiation along with worsening renal functions, low albumin levels, and volume overload is associated with poor outcomes.